WDR26 is a new partner of Axin1 in the canonical Wnt signaling pathway - Goto, Toshiyasu (FEBS Lett, 2016)
The stability of β‐catenin is very important for canonical Wnt signaling. A protein complex including Axin/APC/GSK3β phosphorylates β‐catenin to be degraded by ubiquitination with β‐TrCP. In the recent study, we isolated WDR26, a protein that binds to Axin. Here, we found that WDR26 is a negative regulator of the canonical Wnt signaling pathway, and that WDR26 affected β‐catenin levels. In addition, WDR26/Axin binding is involved in the ubiquitination of β‐catenin. These results suggest that WDR26 plays a negative role in β‐catenin degradation in the Wnt signaling pathway.